Evaluating oral health status in elderly Irula tribes of Tamil Nadu by using the Geriatric Oral Health Assessment Index - Margret Beaula Alocious Sukumar; Roshni Mary Peter; Alex Joseph (Journal of Family Medicine and Primary Care)
Introduction: Oral diseases are a significant global health issue, with over 3.5 billion cases worldwide. Caries and periodontitis are primary contributors to tooth loss, which not only incurs significant rehabilitation costs but also profoundly affects overall well-being. Tribal communities represent a notable indigenous segment, comprising 8.6% of India’s total population, primarily concentrated in the central and western regions. This study assesses the oral health-related quality of life (OHRQoL) among the elderly Irula population by using the Geriatric Oral Health Assessment Index (GOHAI). Methods: A cross-sectional research was undertaken in the Irula settlements of Thiruvallur district, Tamil Nadu, focusing on inhabitants over 60 years who had lived there for at least 6 months. People who were chronically ill or who refused to agree were excluded. Data were gathered using a questionnaire that included demographic information, economic status, personal habits, and health issues. OHRQoL was evaluated using the GOHAI, and descriptive statistics such as range, mean, and standard deviation (SD) for continuous variables were used. To account for possible confounders such as age, education, and socioeconomic status, multivariate analysis was performed using logistic regression. Results: This study results comprised mostly females (76.4%) and individuals aged 60–64 years (44.8%). Most participants were Hindu (94.1%), married (72.5%), and illiterate (61.9%). A majority lived in nuclear families (87.6%) and were agricultural laborers (60.0%). Many participants never experienced limitations in eating due to dental issues (64.0%). Gender, education, and physical comorbidities significantly influenced OHRQoL, with females and those with higher education reporting better quality of life. Conclusion: The study underscores the significant impact of oral health on the quality of life among the elderly Irula population. Factors such as gender, education, and physical comorbidities play crucial roles in OHRQoL. The findings highlight the need for targeted oral health interventions and further research to address disparities and improve oral health outcomes in this underserved population.